THE RELATIONSHIP BETWEEN THE USE OF 3-MONTH INJECTABLE BIRTH CONTROL WITH WEIGHT GAIN INWOMEN BIRTH CONTROL ACCEPTORS AT PMB SARI MAHDALENI, BENGKONG DISTRICT, BATAM CITY IN 2023 - Poppy Sandra; Mediana Sembiring; Wulan Dahyufi; Christina Sitindaon; Sartika Julianti (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
According to the World Health Organization (WHO) (2018) contraceptive use has increased in many parts of the world, especially in Asia and Latin America and lowest in Sub-Saharan Africa. Globally, modern contraceptive use has increased significantly from 54% in 1990 to 57.4% in 2014. Regionally, the proportion of couples of childbearing age 15-49 years who report the use of modern contraceptive methods has increased for at least the last 6 years. In Africa from 23.6% to 27.6%, in Asia it has increased from 60.9% to 61.6%, while Latin America from the Caribbean rose slightly from 66.7% to 67.0%. The coverage of new and active family planning participants in Indonesia in 2021 with the number of couples of childbearing age (PUS) is 47,019,002. New birth control comorbidities (16.15%) included injections (49.67%), birth control pills (25.14%), condoms (5.68%), implants (10.65%). UID (Intra Uterine Device) as much (7.15%), female surgical method (MOW) As. The purpose of this study is to determine the effect of using 3-month injectable birth control with weight gain in women birth control acceptors at PMB Sari Mahdaleni, Bengkong District, Batam City in 2023. The research design is an analytical survey with a cross sectional approach which is a study of the relationship between two variables in a situation or a group of subjects carried out to see the relationship between other variables (Notoadmodjo, 2010). Which aims to determine the relationship between the use of 3-month injectable birth control with weight gain in female birth control acceptors at PMB Sari Mahdaleni, Kec. Bengkong, Batam City in 2023